2021
DOI: 10.1038/s41598-021-86052-1
|View full text |Cite
|
Sign up to set email alerts
|

Retinitis pigmentosa is associated with shifts in the gut microbiome

Abstract: The gut microbiome is known to influence the pathogenesis and progression of neurodegenerative diseases. However, there has been relatively little focus upon the implications of the gut microbiome in retinal diseases such as retinitis pigmentosa (RP). Here, we investigated changes in gut microbiome composition linked to RP, by assessing both retinal degeneration and gut microbiome in the rd10 mouse model of RP as compared to control C57BL/6J mice. In rd10 mice, retinal responsiveness to flashlight stimuli and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 85 publications
1
18
0
Order By: Relevance
“…Another retinal disease influenced by the gut microbiome is the RP. Kutsyr et al (2021) have shown, in an experimental mouse model, that changes in gut microbiome composition are linked to RP. They observed some retinal degenerative abnormalities, such as deterioration of both retinal responsiveness to light stimuli and visual acuity, in animals with retinitis pigmentosa and with changes in gut microbiome.…”
Section: Gut-eye Axis and Retinal Diseasesmentioning
confidence: 98%
See 2 more Smart Citations
“…Another retinal disease influenced by the gut microbiome is the RP. Kutsyr et al (2021) have shown, in an experimental mouse model, that changes in gut microbiome composition are linked to RP. They observed some retinal degenerative abnormalities, such as deterioration of both retinal responsiveness to light stimuli and visual acuity, in animals with retinitis pigmentosa and with changes in gut microbiome.…”
Section: Gut-eye Axis and Retinal Diseasesmentioning
confidence: 98%
“…On the contrary, affected mice were missing the most common genetic variants (Rikenella spp., Muribaculaceae spp., Prevotellaceae UCG-001 spp., and Bacilli spp.) typical of a healthy gut microbiome (Kutsyr et al, 2021). The link between gut microbiome changes and ocular diseases has been explained by several mechanisms (Nayyar et al, 2020).…”
Section: Gut-eye Axis and Retinal Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the rd10 RP mouse model, Kutsyr O. et al. ( 262 ) related alterations in the composition profiles of the gut microbiome to RP. Compared to healthy mice, the gut microbiome of rd10 mice had reduced ASV richness and α diversity.…”
Section: Gut Microbiome and Microglial Activitymentioning
confidence: 99%
“…For instance, a recently identified peripherin rare haplotype variant can cause impairments of photoreceptor outer segment renewal and phototransduction [140], which is closely linked with retinitis pigmentosa punctata albescens (RPA), a non-syndromic retinal degeneration. In addition to genetic factors, other factors are closely associated with pathogenesis of RP, including inflammation [141,142], oxidative stress [143], and gut microbiota [144]. To date, the treatment strategies of RP mainly include supplementation with vitamin A, prosthetics, or gene therapy, although these treatments are not without controversies and limitations.…”
Section: Retinitis Pigmentosa (Rp)mentioning
confidence: 99%